2010
DOI: 10.4238/vol9-2gmr823
|View full text |Cite
|
Sign up to set email alerts
|

No relationship found between -1438A/G polymorphism of the serotonin 2A receptor gene (rs6311) and major depression susceptibility in a northeastern Thai population

Abstract: ABSTRACT. Several lines of evidence suggest a molecular role of -1438A/G single nucleotide polymorphism in the 5-HTR2A gene promoter (rs6311) in regulating the expression of this gene, making rs6311 polymorphism a promising candidate for an association study. We looked for a possible association between rs6311 polymorphism and major depressive disorder (MDD) in a northeastern Thai population. We included 180 patients with MDD and 183 unrelated healthy controls in our study. Genotyping was performed using PCR-R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 29 publications
1
8
0
Order By: Relevance
“…Although this finding was consistent with the results of some previous research [47,48], other studies [49,50] obtained the opposite result, which may be attributed to the use of different sample populations or the influence of regional differences. Logistic regression analysis was used to examine the relationship between T102C and A-1438G genotypes and the risk of mental health problems.…”
Section: Discussionsupporting
confidence: 92%
“…Although this finding was consistent with the results of some previous research [47,48], other studies [49,50] obtained the opposite result, which may be attributed to the use of different sample populations or the influence of regional differences. Logistic regression analysis was used to examine the relationship between T102C and A-1438G genotypes and the risk of mental health problems.…”
Section: Discussionsupporting
confidence: 92%
“…Several studies show negative associations between the T102C polymorphism and MDD [13][14][15]. Furthermore, the A-1438G polymorphism of the HTR2A gene is reported to be significantly associated with MDD [16], while there are also negative associations between this SNP and MDD [13,17].…”
Section: Introductionmentioning
confidence: 94%
“…The A-1438G polymorphism of HTR2A gene Among all 9 articles on HTR2A A-1438G polymorphism and MDD [13,16,17,20,21,33,[36][37][38], a total of 1,510 patients and 2,281 controls were included. Significant heterogeneity was identified for the allelic and genotypic analysis of A-1438G (for A vs. G: P = 0.003; for AA vs. AG ?…”
Section: Meta-analysismentioning
confidence: 99%
See 1 more Smart Citation
“…A Japanese study has revealed that SNPs in HTR3B are associated with depression in female patients based on linkage disequilibrium (LD) (Yamada et al, 2006). Hammer et al (2012) have confirmed rs1062613, rs1176744, and rs3831455 in the HTR3A and HTR3B genes, and the HTR3B variant rs1176744 as predisposing factors for BPD (Tencomnao et al, 2010;Tee et al, 2010). Niesler et al (2001)'s findings suggest that c.178C>T (Pro16Ser) is an allele responsible for susceptibility to BPD.…”
Section: Introductionmentioning
confidence: 96%